Gargoyle holding Flagstaff - Ghosh, Ayan (2023)
Gargoyles are another design element Frederick W. Stevens incorporated from Venetian Gothic architecture. Gargoyles, chimeras and griffons became very popular motifs in cathedrals, churches and castles in the Middle Ages in Europe. In Mumbai, they appear extensively in many of Stevens’ buildings, notably more at CSMT. At the BMC building, they are used sparingly, perched on top of turrets.